ECONOMIC PERFORMANCE AND ITS FACTORS: 5 YEARS OBSERVATION OF MANUFACTURING COMPANIES IN INDONESIA - Eksandy, Arry; Sofia, Irma Paramitha; Nurhidayah, Fitriyah (Universitas Muhammadiyah Tangerang, 2022)
The purpose of this study was to determine the effect of competitive advantage, corporate social performance, business strategy on economic performance in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The time period of the study is 5 years, started from 2014-2018. The population of this study includes all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. The sampling method used in this study is purposive sampling. Based on predetermined criteria obtained 12 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. Data were analyzed using Eviews 9.0 with the analytical method used was regression logistic data panel analysis. The results showed that competitive advantage have a negative effect on economic performance, business strategy have a positive effect on economic performance while corporate social performance have no effect on economic performance.Keyword: economic performance, competitive advantage, corporate social performance, business strategy